The Northern Pacific, main street of the Northwest : - Wood, Charles R. (Superior Pub. Co., 1968)
The history of the Northern Pacific stretches back over 100 years to its formal beginning, the signing of the charter by President Lincoln in 1864 to build the road from the Great Lakes to the Pacific Northwest.